FAKTORâFAKTOR YANG MEMPENGARUHI INDEPENDENSI AUDITOR - Doni, 13.05.52.0118; Himmawan, Arief (Students Journal of Accounting and Banking, 2017)
The deterioration of the auditor independence lately become the main cause of bankruptcies and corporate scandals in different companies in the world. Companies such as Enron case in the United States is manipulating financial statements aided by the firm Arthur Andersen to make investors remain interested in the shares sold Enron. The population in this study were all auditors working in the public accounting firm in Central Java and Yogyakarta. Sampling was done by using a convenience sampling method and the total sample of 73 respondents. Primary data collection method used is the questionnaire. Data were analyzed using multiple linear regression model. The results showed that the intervention of client management and relationship duration audit positive effect on auditor independence, while the termination of audit, audit tight time budget and no significant negative effect on the independence of auditors. While the audit fees but not significant positive effect on the auditor independence.Keywords:Â Client Management Interventions, Termination of Auditors, High Audit Fees, Audit Tight Time Budget, Length of Relationship with The Audit Client and Auditor Independence